Myocardial Infarction in Neonates: A Diagnostic and Therapeutic Challenge - Manuel Rodríguez Martínez; Eladio Ruiz González; Anna Parra-Llorca; Máximo Vento Torres; Marta Aguar Carrascosa (Case Reports in Pediatrics)
Neonatal acute myocardial infarction is an uncommon entity. We describe the case of a 4-day-old term baby who presented with respiratory distress and distal acrocyanosis. The chest radiograph demonstrated cardiomegaly without pleural effusion, and examination revealed hepatomegaly. An electrocardiogram revealed QS pattern in leads I, aVL, and V6, suggestive of ischemia. Cardiac enzymes were elevated, and echocardiogram revealed moderate left ventricular dysfunction with a thrombus at the level of the left atrial appendage. The patient required hemodynamic stabilization, vasodilatation to avoid congestive heart failure, and anticoagulation with heparin and aspirin. In the context of this unusual diagnosis, we reviewed our experience over the last 17 years as well as the existing literature on neonatal myocardial infarction.